Can Quantum Mechanics and Relativity be Considered Per se Complete? - A discussion on Quantum Mechanics and Relativity in Full Space-Time Domain - Li, Yuanjie; Zhang, Lihong; Dong, Peng (JOURNAL OF ADVANCES IN PHYSICS, 2018)
This paper points out the incompleteness of the traditional quantum mechanics and relativity, which is embodied in space-time domains of definition, not in physical quantities for description. The real time and space are not continuous. The phenomena called â€œghost-like long-range actionâ€ by Einstein in fact occur in the time discontinuity points, that is, Time Quantum Worm Holes put forward by Hawking. This paper also gives an essential difference between the macroscopic random motion and the microscopic random motion, which is critical for understanding wave-particle duality.